THE IMPACT OF THE METACOGNITIVE AND BEHAVIORAL FACTORS OF CULTURAL INTELLIGENCE ON FOREIGN BRAND ACCEPTANCE - Zdravkovic, Stefan; Peković, Jelena (The European Journal of Applied Economics, 2021)
The aim of the paper is to show the influence of cultural intelligence in the acceptance of foreign brands and how these insights can help multinational companies in shaping and presenting their brands so that they are better accepted in different cultural environments. Cultural intelligence consists of four factors, two of which have been analyzed for the purposes of this paper - the metacognitive and behavioral factors. The metacognitive cultural dimensions are useful for the individual uses in order to obtain certain knowledge about a particular culture. Behavioral cultural intelligence represents the ability to adapt an individual to verbal and non-verbal behaviors according to the situation in culturally diverse environments. The results of the empirical research proved a statistically significant positive impact of the behavioral element of cultural intelligence on the acceptance of foreign brands by consumers, while the influence of the metacognitive factor on the acceptance of foreign brands is not statistically significant, which is different from most of the empirical studies conducted so far.
Keywords: cultural intelligence, metacognitive factor, behavioral factor, foreign brand